Full genomic sequence of the HLA‐C*15:02:03 allele identified by next generation sequencing. (15th February 2022) - Liacini, Abdelhamid; Peters, Lindsey; Gravante, Christopher; Mancini, Shannon; Geier, Steven
Abstract : Full‐length sequence of HLA‐C*15:02:03 covers all introns and exons and the 3′ UTR.